2022
DOI: 10.1038/s41598-021-04454-7
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of umbilical cord-derived mesenchymal stem cells promotes the recovery of thin endometrium in rats

Abstract: The endometrium plays a critical role in embryo implantation and pregnancy, and a thin uterus is recognized as a key factor in embryo implantation failure. Umbilical cord mesenchymal stem cells (UC-MSCs) have attracted interest for the repair of intrauterine adhesions. The current study investigated the repair of thin endometrium in rats using the UC-MSCs and the mechanisms involved. Rats were injected with 95% ethanol to establish a model of thin endometrium. The rats were randomly divided into normal, sham, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…After confirming that umbilical cord mesenchymal stem cells (UCMSCs) can improve uterine appearance and morphological characteristics, a study analyzed the differential expression of miRNAs in the IUA model group and the MSCs treatment group ( Zhang et al, 2022b ). Compared with the model group, 55 miRNAs were up-regulated and 59 miRNAs were down-regulated in the treatment group.…”
Section: Potential Therapeutic Role Of Ncrna In Intrauterine Adhesionmentioning
confidence: 99%
“…After confirming that umbilical cord mesenchymal stem cells (UCMSCs) can improve uterine appearance and morphological characteristics, a study analyzed the differential expression of miRNAs in the IUA model group and the MSCs treatment group ( Zhang et al, 2022b ). Compared with the model group, 55 miRNAs were up-regulated and 59 miRNAs were down-regulated in the treatment group.…”
Section: Potential Therapeutic Role Of Ncrna In Intrauterine Adhesionmentioning
confidence: 99%
“…IUA can interfere with the embryo's implantation and development, resulting in decreased or even full loss of intrauterine volume, female infertility, and recurrent miscarriages [76]. The thin endometrial model exhibits a higher degree of fibrosis than normal controls, which is thought to be a crucial component in embryo implantation failure [77]. The key question is why fibrosis doesn't occur during normal early pregnancy?…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted November 14, 2022. ; https://doi.org/10.1101/2022.11.12.516251 doi: bioRxiv preprint differentiation into endometrial cell types (13)(14)(15)(16). The secretome and biological characteristics of MSCs vary based on tissue source (17,18); however, both BM-MSCs and UC-MSCs promote endometrial regeneration in rodent models (12).…”
Section: Introductionmentioning
confidence: 99%
“…Studies with rodent models and small clinical trials have shown that nonhematopoietic MSCs from different tissue sources can contribute to endometrial repair after injury (12). In rat models of endometrial injury, BM-MSCs and umbilical cord (UC) MSCs aid endometrial repair through paracrine actions on the endometrium as well as differentiation into endometrial cell types (13)(14)(15)(16). The secretome and biological characteristics of MSCs vary based on tissue source (17,18); however, both BM-MSCs and UC-MSCs promote endometrial regeneration in rodent models (12).…”
Section: Introductionmentioning
confidence: 99%